(untitled) (Dhaka University Journal of Biological Sciences, 2022)
Toxoplasma gondii (T. gondii) is an intracellular protozoan parasite that causes the disease Toxoplasmosis. Acute infection of T. gondii in pregnant women is dangerous because the parasite can transmit into developing foetus and can cause congenital toxoplasmosis. To assess the prevalence of T. gondii infection, its association with pregnancy and the impact of this parasite on generating oxidative stress, ninety-two pregnant women and sixty-five age matched non-pregnant control subjects were enrolled in this study. Using an immunological assay with a rapid test cassette, T. gondii specific IgG antibody was detected in 25% pregnant women while it was found only 9.2% in non-pregnant healthy control subjects, suggesting that a higher percentage of pregnant women carried chronic T. gondii infection compared to control subjects. Anti-T. gondii IgM was also tested and found to be positive in only 3.3 % pregnant women as compared to control. Polymerase Chain Reaction analysis was carried out with the DNA isolated from blood of both anti-T. gondii IgM and IgG positive pregnant women and was found to be negative for T. gondii REP-529 gene, suggesting a chronic infection. Our data suggest that pregnant women who were in contact with cat in their third trimester of pregnancy demonstrated a significantly higher association with acquiring infection. Furthermore, to determine any association of T. gondii infection with oxidative stress in pregnant women, oxidative stress markers were assessed in plasma samples. The total oxidative stress was found to be higher in T. gondii positive subjects compared to T. gondii negative samples whereas total antioxidant defence was observed to be slightly decreased in T. gondii positive pregnant women. It can primarily be said that chronic T. gondii infection in pregnant women may increase oxidative stress and this, therefore, may act as a risk factor for congenital toxoplasmosis. Dhaka Univ. J. Biol. Sci. 31(1): 79-91, 2022 (January)